1989
DOI: 10.1152/jappl.1989.66.3.1373
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway and respiratory muscle responses to continuous negative airway pressure

Abstract: To determine upper airway and respiratory muscle responses to nasal continuous negative airway pressure (CNAP), we quantitated the changes in diaphragmatic and genioglossal electromyographic activity, inspiratory duration, tidal volume, minute ventilation, and end-expiratory lung volume (EEL) during CNAP in six normal subjects during wakefulness and five during sleep. During wakefulness, CNAP resulted in immediate increases in electromyographic diaphragmatic and genioglossal muscle activity, and inspiratory du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 0 publications
2
45
0
2
Order By: Relevance
“…More recently, methods have been developed for quantifying active neuromuscular responses in sleeping subjects, and a defect in these active responses has been demonstrated in patients with sleep apnea compared with normal subjects. This defect in neuromuscular control was independent of age, obesity, and sex (86), and may be caused by sleep-related reductions in dilator activity during sleep compared with wakefulness (87,88) or by a loss of compensatory responses during sleep (87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99). Thus, current evidence indicates that sleep apnea is associated with fundamental disturbances in upper airway mechanical (68,100,101) and neuromuscular control (80,(102)(103)(104)(105)(106)) (see Figure 1, left), and suggests that a combined defect is required to produce sleep apnea (86).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 98%
“…More recently, methods have been developed for quantifying active neuromuscular responses in sleeping subjects, and a defect in these active responses has been demonstrated in patients with sleep apnea compared with normal subjects. This defect in neuromuscular control was independent of age, obesity, and sex (86), and may be caused by sleep-related reductions in dilator activity during sleep compared with wakefulness (87,88) or by a loss of compensatory responses during sleep (87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99). Thus, current evidence indicates that sleep apnea is associated with fundamental disturbances in upper airway mechanical (68,100,101) and neuromuscular control (80,(102)(103)(104)(105)(106)) (see Figure 1, left), and suggests that a combined defect is required to produce sleep apnea (86).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 98%
“…Respiratoryrelated evoked potentials did not change after OSAS treatment. (21); (2) the fact that the upper airway response to disparate stimuli, such as hypercapnia and inspiratory loading, is similar (22); (3) the rapid timing of the response compared with voluntary activation (23); and (4) changes in the response to loading during sleep compared with wakefulness (24). The upper airway contains pressure receptors in the mucosa of the nasopharynx and larynx (25).…”
Section: Upper Airway Neuromotor Controlmentioning
confidence: 99%
“…Besides, decreases in respiratory reactance have previously been observed during resistive or elastic loading, and attributed to an increase in tissue elastance resulting from increased respiratory muscle activity [27]. As it has been reported that CNAP application results in an increase in diaphragmatic and parasternal intercostal electromyographic activity [10,28], the Ers response to CNAP presently observed may be explained by the enhanced activity of inspiratory muscles. As Irs remained unchanged when the CNAP level was decreased, the signi®cant increases observed in RF directly result from those in Ers.…”
Section: Respiratory Response To Decreasing Continuous Negative Airwamentioning
confidence: 70%
“…that Rrs became more and more frequency dependent, may be attributed to: 1) the increase in Rti resulting from reduced lung volume, which has been reported to be more pronounced at the lower frequencies [25]; and 2) the occurrence and development of series and/or parallel gas redistribution [21]. Series gas redistribution is mainly due to UA shunt compliance, whose in¯uence on Rrs was probably reduced under CNAP, due to the increased activity of UA dilating muscles [10]. Consequently, it is more probable that parallel gas redistribution developed within intrathoracic airways, as a result of the pulmonary inhomogeneities promoted by the CNAPinduced decrease in lung volume.…”
Section: Respiratory Response To Decreasing Continuous Negative Airwamentioning
confidence: 96%